Análisis documental de la influencia del clima organizacional en colaboradores de diversos sectores económicos latinoamericanos durante la última década - Forero Puerto, Yennifer Alejandra (Universidad Antonio Nariño, 2022)
The present research study was carried out with a documentary analysis, whose objective was to review, based on Latin American scientific literature, the influence of organizational climate on collaborators in various economic sectors during the last decade, where studies were identified that allowed describing this category and each of the subcategories such as communication, motivation, leadership, satisfaction, stress, self-esteem and performance.